Construction of Civilization Periodization in the History of Islamic Education - Dani Samdani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this journal article is to refer to efforts to build or form a re-understanding of historical periodization in the development of Islamic education throughout history, to identify and understand certain phases or periods in Islamic civilization related to Islamic education. The method applied in this research is the library research method, or what is called (library research), where researchers collect data relevant to the problem being studied. Collecting data with relevant previous research results is support for research on the construction of the periodization of the civilization of the history of Islamic education. The description process, namely uses data analysis techniques in the form of content analysis (content analysis) so that existing data will be described in depth from the data that researchers have collected. According to Ahmad Usairy in his book reveals that, the periodization of Islamic history is completely divided into several periods including The Classical Historical Period began from the time of the Prophet Adam until before the sending of the Prophet Muhammad SAW). Historical Period of the Prophet Muhammad SAW in the year (570-632 AD, Historical Period of Khulafa' Rashidin in the year (632-661 AD). Period of Bani Umaiyah Government in the year (661-749 AD). The period of Bani Abbasid rule in the year (749-1258 AD). The period of Mamluk rule (1250-1517 AD). The period of Ottoman rule (1517-1923 AD) and the period of the contemporary Islamic world (1922-2000 AD).